Synthesis of GO-ZnO via impregnation method for fluoride removal in wastewater / Mohamad Hanafi Mohamad Rosli, Nurulhuda Amri and Norhusna Mohamad Nor - Mohamad Rosli, Mohamad Hanafi; Amri, Nurulhuda; Mohamad Nor, Norhusna (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
High concentration of fluoride in wastewater discharge from various industries is threatening the environment due to its hazardous effects and properties. This research work aims to develop an efficient adsorbent for fluoride removal in wastewater. Graphite oxide (GO) was impregnated with ZnO nanoparticles as an adsorbent, and the effect of synthesis parameters of GO-ZnO adsorbent for fluoride removal were studied (sonication temperature, synthesis time, and ratio of GO to ZnO). The surface functional groups of these synthesized adsorbents were analyzed by using FTIR. The synthesis parameters that contribute to the highest adsorption capacity and percentage removal are 5:1 ratio of GO-ZnO, 45 ºC of sonication temperature and 60 minutes of synthesis time, respectively. The highest value of adsorption capacity obtained from the fluoride removal is 55.5 mg/g. The functional groups contained in the GO-ZnO adsorbent are hydroxyl group (O-H), C=O group, aromatics group, carboxyl group (C-O), epoxy group and alkoxy group. These functional groups showed significant impact towards fluoride adsorption due to the bonding of fluoride ion to the functional groups.